Infracciones en los cruces peatonales en Costa Rica: explorando factores que afectan el comportamiento - Araya-Porras, Enoc; Mora-Calderón, Andrey; Aguero-Valverde, Jonathan (Universidad de Costa Rica, 2022)
It is necessary to analyze pedestrian behavior at crossings to improve their safety and mobility. Mid-block pedestrian crossings are structures that facilitate the mobility of pedestrians, safeguarding them from vehicular traffic; however, illegal crossing by pedestrians is an everyday occurrence and represents a risk to their safety. The purpose of this study is to evaluate the relationship between different human and road factors and the decision to illegally cross signalized mid-block crossings. Several human factors such as age, gender, waiting time in traffic light, use of the pushbutton and individual or group crossing, as well as road characteristics such as the length of traffic light phase, length of crossing, and vehicular volume were analyzed. To collect information about these variables this study recorded a one-hour video in six selected crosswalks within the Montes de Oca County in Costa Rica. A total of 1,707 crossings were recorded, 10.6% of which corresponded to instances of illegal crossing. After applying a logit model, this research found that traffic volume, pedestrian red-light time, waiting time, vehicle illegal crossing and group crossings reduced the probability of violations by pedestrians. On the other hand, minimum traffic light time and crossing length increased the possibility of pedestrian illegal crossings. This study concluded that the traffic light cycle is an important variable that must be rigorously analyzed to ensure pedestrian's compliance with traffic lights, which will improve the safety of the pedestrian mid-block crossings.